EFFICIENCY OF GENETIC DIVERSITY ASSESSMENT OF LITTLE-POD FALSE FLAX (CAMELINA MICROCARPA ANDRZ. EX DC.) IN UKRAINE USING SSR AND TBP MARKER SYSTEMS - Sakharova, V. H.; Blume, R.Ya.; Rabokon, A.N.; Pirko, Ya.V.; Blume, Ya.B. (Reports of the National Academy of Sciences of Ukraine, 2023)
The molecular genetic diversity of Ukrainian little-pod false flax (Camelina microcarpa Andrz. ex DC.) was assessed using two methods: tubulin-based polymorphism (TBP), which is based on length polymorphism of the first intron of β-tubulin genes, and microsatellite sequences (SSR — simple sequence repeats). The study was aimed to investigate the genetic diversity among the analyzed little-pod false flax accessions and determine the comparative effectiveness of the employed molecular methods. Furthermore, the suitability of prioritizing the TBP method for the analysis of herbarium specimens, considering the limited plant material and potential DNA damage caused by long-term storage, was demonstrated.